A Survey of Association Rule Mining for Customer Relationship Management - Gautam, Ajit Pratap Singh; Sharonova, Natalia Valeriyevna (My University, 2014)
Data mining technique is most frequently used in Customer Relationship Management field. There are many data mining algorithm and methods can be used in solving CRM problems. Association Rule Mining technique is widely used in CRM application. Various algorithms has been proposed by various researches. This paper is an effort to analyze these algorithms in view of their implementation in Customer Relationship Management.